AUDIT KESELAMATAN JALAN RAYA BUKITTINGGI- PAYAKUMBUH - Ahmad Ramadhani; Surya Eka Priana; Febrimen Herista (Ensiklopedia Research and Community Service Review, 2022)
A traffic accident is an event that cannot be avoided, an event where a motorized or non-motorized vehicle comes into contact with each other and causes both material and non-material losses and loss of life. Some of the factors that have the potential to cause accidents are the indiscipline factor in using the vehicle and disobeying existing traffic signs. Jalan Raya Bukittinggi-Payakumnbuh is a class III collector road with a width of ± 9 meters with a sidewalk. Along the audited road are shops and Ford De Kock University. This contributes greatly to attracting the number of people traveling and the high volume of vehicles crossing the Bukittinggi-Payakumbuh highway. Therefore, research was carried out starting from STA 0+100 – STA 1+500, this study aims to analyze road safety by using inspections with the AKJ (Road Safety Audit) checklist table with Y/N answers, such as general condition items, alignment roads, intersections, turning lanes, street lighting and road signs and markings. From the results obtained, the stopping sight distance for an operational speed of 50.07 km/sec in the calculation of the stopping sight distance, the distance of 52.88 meters is still below the design standard and for the ready sight distance of 161.45 meters, the maximum viewing distance of the plan is 350 meters. Based on the AKJ table (road safety audit) for the Bukittinggi-Payakumbuh highway, the highest feasible is from the aspect of signs and road markings of 68.75%, the lowest feasible value is general condition of 50%. The driver factor is the factor causing the highest traffic accidents, namely 26 accidents out of 38 accidents (68.43%), the rest is the vehicle factor, namely 12 accidents out of 38 accidents (31.57%). In order to overcome the problems on the audited roads, it is necessary to repair and complete the signs that are lacking and the maintenance of other complementary facilities in order to reduce traffic accidents. Keywords: Road safety audit, Accident, Stopping visibility, Ready visibility, Bukittinggi-Payakumbuh Highway